Preventive culture on occupational safety in the assistance staff of a health center in Huanuco - Pacheco-Santillan, Sherly L. (2021)
Objective. To determine the preventive culture on occupational safety in the assistance staff of a health center. Methods: An observational, prospective, cross-sectional study with a simple descriptive design was conducted with 96 healthcare workers from the Potracancha Health Center. A questionnaire was used to collect data. For the inferential analysis of the results, the chi-square test was used for a sample. Results. In general, 88.5% (85) of the workers had a perception of medium level of the preventive culture on occupational safety, being this a statistically significant result (p = 0.000). Already by dimensions, leadership commitment, leadership involvement, fairness and collective commitment and learning have been valued at a medium level and “risk awareness” and “prevention trust” have been perceived at a low and high level, respectively, all with p < 0.05. Conclusion: The preventive culture on occupational safety in the assistance staff of the Potracancha Health Center is of medium level.